ASSESSING STUDENTS’ WRITING ABILITY IN A NARRATIVE TEXT - Anggi Kristiana Wardana; M. Zaini Miftah; Akhmad Ali Mirza (IKIP Siliwangi, 2022)
Assessing writing is one of the most difficult case in language test, because good writing is so sought out by master of the higher education and plenty of establisments are require. The teachers must spend a whole lot of time to ensuring that their writing evaluation are accurate and reliable. This study is primarily based totally at the desires to recognize the students’ writing ability in a narrative text of the fourth semester students of English Education by using quantitative method with a retrospective evaluation research. The population of the study was 122 students and the sample elected were 40 students. Writing test is used for the instrument of this study, which distributed as online by using Google Form. The data were analyzed by Ms. Excel and SPSS, the result confirmed that the students have good writing ability in a narrative text. The mean score achieved was 81.31. It was in the good category. But, there were 3 students categorized into poor and fair. This result is in line with the assessing students’ ability in a narrative text by using scoring rubric that available in this study. Keywords: Assessment Writing, Ability, Narrative Text